Incidence and determinants of nosocomial infection among hospital admitted adult chronic disease patients in University of Gondar Comprehensive Specialized Hospital, North–West Ethiopia, 2016–2020 - Taye, Zewdu Wasie; Abebil, Yaregal Animut; Akalu, Temesgen Yihunie; Tessema, Getahun Mengistu; Taye, Eden Bishaw (Frontiers in Public Health, 2023)
Background: Nosocomial infections are major public heath problem which affects more than 100 million patients in each year globally. This leads to prolonged hospital stays, a high rate of mortality, and a huge financial burden to patients and the healthcare system. This study aimed to determine the incidence of nosocomial infections and determinant factors among admitted adult chronic illness patients at the University of Gondar Comprehensive Specialized Hospital, Northwest Ethiopia. Methods: An institutional-based retrospective follow-up study design was employed among 597 respondents. The secondary data was collected from April, 15 to May 15, 2021. A computer-generated random sampling technique was used to select a total of 599 patients using Open-epi software. Data were collected using structured checklists. Epi-Data version 4.6 and STATA 16 were used for data entry and analysis respectively. Cox-regressions (univariable and multivariable) were performed to identify statistically significant variables. Adjusted hazard ratio with 95% CI was used to declare statistically significant variables based on p < 0.05 in the multivariable Cox-regression model. Results: A total of 597(99.6%) adult chronic illness patients were included in the study. Of these, 53 (8.88%) participants developed nosocomial infections and the incidence rate of nosocomial infection was 6.6 per 1,000 person-days observation. In this study, not taking antibiotics (AHR= 2.74, 95% CI: 1.49, 5.04), using mechanical ventilation (AHR=2.67, 95% CI: 1.36, 5.26), being on urinary catheter (AHR=4.62, 95% CI: 2.22, 9.65), being on intravenous catheter (AHR=3.42, 95% CI: 1.22, 9.61) and length of hospital stay >20 days (AHR= 2.66, 95% CI: 1.43, 4.94) were significantly associated with nosocomial infections. Conclusions: The findings have indicated that the incidence of nosocomial infection was low. No taking antibiotics, intravenous insertion, mechanical ventilation, urinary catheterization, and length of hospital stay were the predictors for the development of nosocomial infection. Therefore, we recommend that the healthcare providers need to emphasis on infection prevention and control in the institution on these factors that have a significant effect on nosocomial infection.